2021
DOI: 10.1002/cssc.202100294
|View full text |Cite
|
Sign up to set email alerts
|

How Comparable are Microbial Electrochemical Systems around the Globe? An Electrochemical and Microbiological Cross‐Laboratory Study

Abstract: In memory of Dr. Alessandra ColomboA cross-laboratory study on microbial fuel cells (MFC) which involved different institutions around the world is presented. The study aims to assess the development of autochthone microbial pools enriched from domestic wastewater, cultivated in identical single-chamber MFCs, operated in the same way, thereby approaching the idea of developing common standards for MFCs. The MFCs are inoculated with domestic wastewater in different geographic locations. The acclimation stage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Concerning electroactive bacteria, researchers have mainly focused on model organisms such as Shewanella and Geobacter species to understand the fundamentals of EET, and therefore the comparison in this review naturally focuses on these model organisms. However, Light et al ( 2018 ), Santoro et al ( 2021 ) as well as Edel, Philipp, Lapp, Reiner, and Gescher ( 2022 ) have shown that there is an enormous number of organisms that perform EET based on flavins or c ‐type cytochromes that have not been considered in BES applications yet. The diversity of these unknown metabolic pathways and microorganisms could be the foundation for advanced BES applications.…”
Section: Future Direction Of Bes Performance Optim...mentioning
confidence: 99%
“…Concerning electroactive bacteria, researchers have mainly focused on model organisms such as Shewanella and Geobacter species to understand the fundamentals of EET, and therefore the comparison in this review naturally focuses on these model organisms. However, Light et al ( 2018 ), Santoro et al ( 2021 ) as well as Edel, Philipp, Lapp, Reiner, and Gescher ( 2022 ) have shown that there is an enormous number of organisms that perform EET based on flavins or c ‐type cytochromes that have not been considered in BES applications yet. The diversity of these unknown metabolic pathways and microorganisms could be the foundation for advanced BES applications.…”
Section: Future Direction Of Bes Performance Optim...mentioning
confidence: 99%
“…27 However, many of the occurring species have been detected in electrochemically active biofilms or planktonic cultures, such as Thioalkalivibrio sulfidophilus, Acholeplasma sp. and Bacteroidales GZKB119 15,20,[28][29][30] (Table 3).…”
Section: Biomass Composition Of Sulphide Shuttling Communitiesmentioning
confidence: 99%
“…At larger scales (L or m 3 scale), selecting proper mixing conditions is required to increase the contact time between the biofilm and fresh medium, in addition to avoiding pH gradients (Zeppilli et al, 2021). Information available in the literature about design parameters of bioelectrochemical reactors is scarce and lacks standardization of data representation (Santoro et al, 2021). For example, dimension-less numbers (e.g., Reynolds or Newton numbers) or chemical oxygen demand as the total carbon equivalent for the coulombic efficiency calculation must be given to allow proper benchmarking (Krieg et al, 2018a).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%